Optical Coherence Tomography Angiography Predicts Visual Outcomes for Craniopharyngioma in Children by Quantifying Choroidal Capillaries - Zhang, Qing Lin; Wang, Jun Hua; Sun, Li Ying; Wang, Jian Bin; Ma, Yu; Zhang, Yu Qi (Frontiers in Medicine, 2022)
Purpose: To predict the prognosis of craniopharyngioma in children by optical coherence tomography angiography (OCTA). Methods: We evaluated if the relationship between preoperative OCTA of the choroidal capillary density (CCD) and visual outcome continued over long-term visual recovery in 38 patients undergoing craniopharyngioma resection. Patients were evaluated 3 times: one week before surgery (Visit1), followed-up 6 to 10 weeks (Visit2) and 9 to 15 months (Visit3) after surgery. Results: In total 38 patients (70 eyes) with craniopharyngiomas, which included 20(52.6%) males and 18 (47.4%) females, the mean age was 11.8 ± 2.7 years (range: 6-18 years). The age (p=0.71), gender (p=1.00), mean refractive error (p=0.55) and axial length (p=0.23) of 38 volunteers (76 eyes) normal volunteers were matched. After surgery, the cross-compression of patients were relieved. The average visual acuity change in the normal CCD group was 0.07±0.02; the average visual acuity change in the low CCD group was 0.01±0.01, p<0.001. Preoperative CCD value is related to the preoperative BCVA (p <0.001), and the visual function after the long-term follow-up (9-15 months) (p <0.001). The prognosis of CCD has the same trend as the BCVA. Further correlation analysis shows that CCD and BCVA are significantly correlated (r=0.878; p < 0.001). CCD has a weak but significant correlation both with MD (r=0.19; p <0.001) and PSD (r=-0.21; p <0.001). a natural cutoff of CCD is approximately 38(%). With normal CCD group that maximum improvement of BCVA exceeds 0.3 post-operatively, compared eyes in low CCD group that improve by less than 0.03 and even worse after surgery. Conclusions: long-term vision recovery after surgical decompression of craniopharyngiomas in children can be predicted by preoperative by OCTA. Patients with normal CCD before surgery showed a tendency to improve vision; this trend of improvement persisted in subsequent follow-ups. The CCD baseline natural cutoff value for predicting visual prognosis before and after surgery is about 38(%).